2007
DOI: 10.1097/meg.0b013e3282efa40e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics on gut flora, level of endotoxin and Child–Pugh score in cirrhotic patients: results of a double-blind randomized study

Abstract: E. coli Nissle seems to be effective in the restoration of normal colonic colonization and can probably lower endotoxemia in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 9 publications
7
78
2
Order By: Relevance
“…Several studies have demonstrated that modulation of the intestinal microbiota in advanced cirrhosis by probiotics or antibiotics is beneficial for the prevention of bacterial translocation and spontaneous bacterial peritonitis [72,73]. It has been shown that antibiotics prevent hepatic injury and fibrosis induced by CCl4 treatment or a cholinedeficient diet, and that LPS enhances hepatic fibrosis induced by a MCCD [74,75].…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…Several studies have demonstrated that modulation of the intestinal microbiota in advanced cirrhosis by probiotics or antibiotics is beneficial for the prevention of bacterial translocation and spontaneous bacterial peritonitis [72,73]. It has been shown that antibiotics prevent hepatic injury and fibrosis induced by CCl4 treatment or a cholinedeficient diet, and that LPS enhances hepatic fibrosis induced by a MCCD [74,75].…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…Reports on possible influencing of bacterial translocation (and thus the development of SBP) using prokinetics [44,45] or probiotics [46] have appeared in the literature.…”
Section: Preventive Treatmentmentioning
confidence: 99%
“…40 Use of E Coli Nissle strain was reported to result in improvement in liver function, as measured by ChildPugh score, and reduction in endotoxin levels. 41 Those results, however, have not been replicated. These reports indicate the need for large prospective trials to evaluate clinical outcomes of patients with cirrhosis and liver disease treated with probiotics.…”
Section: Other Liver Diseasesmentioning
confidence: 47%